2D Piezoelectric Bi2MoO6 Nanoribbons for GSH‐Enhanced Sonodynamic Therapy. Issue 51 (16th October 2021) - Dong, Yushan; Dong, Shuming; Liu, Bin; Yu, Chenghao; Liu, Jing; Yang, Dan; Yang, Piaoping; Lin, Jun
Abstract: Reducing the scavenging capacity of reactive oxygen species (ROS) and elevating ROS production are two primary goals of developing novel sonosensitizers for sonodynamic therapy (SDT). Hence, ultrathin 2D Bi2 MoO6 –poly(ethylene glycol) nanoribbons (BMO NRs) are designed as piezoelectric sonosensitizers for glutathione (GSH)‐enhanced SDT. In cancer cells, BMO NRs can consume endogenous GSH to disrupt redox homeostasis, and the GSH‐activated BMO NRs (GBMO) exhibit an oxygen‐deficient structure, which can promote the separation of electron–hole pairs, thereby enhancing the efficiency of ROS production in SDT. The ultrathin GBMO NRs are piezoelectric, in which ultrasonic waves introduce mechanical strain to the nanoribbons, resulting in piezoelectric polarization and band tilting, thus accelerating toxic ROS production. The as‐synthesized BMO NRs enable excellent computed tomography imaging of tumors and significant tumor suppression in vitro and in vivo. A piezoelectric Bi2 MoO6 sonosensitizer‐mediated two‐step enhancement SDT process, which is activated by endogenous GSH and amplified by exogenous ultrasound, is proposed. This process not only provides new options for improving SDT but also broadens the application of 2D piezoelectric materials as sonosensitizers in SDT. Abstract : As‐constructed Bi2 MoO6 –poly(ethylene glycol) (BMO‐PEG) nanoribbons (NRs) with piezoelectric properties provide a double‐upgrading sonodynamic therapy. The BMO NRs consume endogenous glutathione (GSH) to disrupt redox homeostasis. Furthermore, it is discovered that the GSH‐activated BMO NRs indicate a higher ultrasound (US)‐triggered reactive oxygen species generation efficiency owing to internal oxygen defects, which predominantly traps electrons to delay the recombination of e − –h + pairs. Unlike conventional sonosensitizers, ultrathin GSH‐activated BMO NRs are piezoelectric, which can maximize the use of US energy to induce polarization, thereby facilitating e − –h + separation and improving the efficiency of sonodynamic therapy.